2017
DOI: 10.4149/neo_2017_406
|View full text |Cite
|
Sign up to set email alerts
|

miR-361-5p suppresses lung cancer cell lines progression by targeting FOXM1

Abstract: Lung cancer is the most common type of cancer and the leading cause of death in worldwide. MicroRNAs are known to be key players in a variety of biological processes, including tumorigenesis. In present study, we investigated the effect of miR-361-5p on lung cancer progression. We found that miR-361-5p was down-regulated in lung cancer. Overexpression of miR-361-5p suppressed lung cancer proliferation and invasion. Mechanistically, FOXM1 was identified as a direct target of miR-361-5p. Furthermore, miR-361-5p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 25 publications
3
31
0
Order By: Relevance
“…Previous studies revealed that FOXM1 could act as a target of miR-361-5p in tumor progression [16,17]. In the present study, GEPIA database showed that FOXM1 was significantly increased in CC tissues compared to ANT tissues (Figure 4(A,B)), which was further confirmed in CC tissues by qRT-PCR and IHC in our studies (Figure 4(C,D)).…”
Section: Sbf2-as1 Regulated Foxm1 Expression Via Mir-361-5psupporting
confidence: 85%
“…Previous studies revealed that FOXM1 could act as a target of miR-361-5p in tumor progression [16,17]. In the present study, GEPIA database showed that FOXM1 was significantly increased in CC tissues compared to ANT tissues (Figure 4(A,B)), which was further confirmed in CC tissues by qRT-PCR and IHC in our studies (Figure 4(C,D)).…”
Section: Sbf2-as1 Regulated Foxm1 Expression Via Mir-361-5psupporting
confidence: 85%
“…Emerging lines of evidence have demonstrated that miRNAs are upregulated or downregulated in NSCLC, and this phenomenon is involved in the regulation of various processes during tumorigenesis and progression, including tumour groWTh, apoptosis, cell invasion and tumour metastasis (34)(35)(36). Therefore, understanding the molecular mechanism that links abnormally expressed miRNAs with NSCLC formation and development may lead to the identification of novel diagnostic and therapeutic targets for NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to PICSAR, some miRNAs were detected in the present study, which have rarely been studied in the field of breast cancer study, but have been shown to play important roles in other fields. For example, miR-361 showed high expression in both MCF-7 and MDA-MB-231 cell lines and has been demonstrated as an antioncogene in lung cancer [48] and endometrial cancer [49], but has not been explored in breast cancer basic research studies. Thus, this molecule may be a novel finding, and further experimental verification is needed.…”
Section: Discussionmentioning
confidence: 99%